2018
DOI: 10.1039/c8ra02087f
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the size effect of graphene nano-platelets (GnPs) on the anti-corrosion performance of polyurethane/GnP composites

Abstract: In this article, polyurethane/graphene nano-platelet (PU/GnP) composites were fabricated via planetary centrifugal mixer (PCM) and cast on polyethylene terephthalate (PET) and copper substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…The Tafel plot provides the corrosion potential (E corr ) and corrosion current (I corr ), and these parameters enable a quantitative comparison between the anti‐corrosion performance of a material. For instance, the enhancement of the anti‐corrosion performance is associated with the tendency for an increase in the E corr and a decrease in the I corr . The two parameters, E corr and I corr , are determined by the intersection point extrapolated cathodic and anodic curves in the Tafel slopes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tafel plot provides the corrosion potential (E corr ) and corrosion current (I corr ), and these parameters enable a quantitative comparison between the anti‐corrosion performance of a material. For instance, the enhancement of the anti‐corrosion performance is associated with the tendency for an increase in the E corr and a decrease in the I corr . The two parameters, E corr and I corr , are determined by the intersection point extrapolated cathodic and anodic curves in the Tafel slopes.…”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to the fact that the smaller size of C750 is not only uniformly dispersed within the PU but also offers a high surface area. This effect considerably contributes to the construction of an efficient filler arrangement that suppresses the diffusion of a corrosive agent onto the Cu substrate . For this reason, PU/GO‐M25 composites show a higher E corr and lower I corr than the PU/C750 composites at the same fillers content.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoplatelets of graphene or graphene oxide (GO) [21][22][23] can be produced chemically [24] or electrochemically [25] in a large amount by exfoliation of graphite. These are appropriate for large scale applications and the costs are much lower than those produced by CVD or on SiC wafers.…”
Section: Introductionmentioning
confidence: 99%
“…Their classifications depend on the thickness, lateral size, and elemental concentration. In any given batch, thickness can vary from 0.34 nm to 100 nm and the number of graphene layers is typically between 10-60 23,24 . This structure leads to the high surface area and stability of GnPs, and research has found that their integration into composites can increase mechanical, thermal and electrical conductivity properties 25 .…”
mentioning
confidence: 99%